Academic resilience: the roles of parent support and peer support - Jumraeni Jumraeni; Septya Suarja; Nur Saqinah Galugu; Muh. Irham Zainuri (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2023)
. This study aims to investigate the relationship between parent support, peer support, and academic resilience. This study used a quantitative method with a correlational design. The sample of the study was 165 students, selected using the purposive sampling technique with the criteria: students at least in the seventh semester and currently working on the final paper at the Faculty of Teacher Training and Education. Peer and parent support was measured using the social support questionnaire developed by the researchers, while academic resilience was measured using The Academic Resilience: Scale-30 (ARS-30). Data analysis was performed using multiple linear regression and assisted by the SPSS 25.00 for Windows application. The results of the study showed that most students (52%) had high resilience; 98% of students had a moderate level of parent support; and all students (100%) had a moderate level of peer support. Based on the partial test results, it can be concluded that there is a relationship between parent support and academic resilience, but no relationship between peer support and academic resilience. However, the results of the simultaneous test showed that peer support and parent support are correlated with academic resilience.